Acute liver failure in an Immunocompetent host:A Diagnostic Dilemma - MAITRA, SOMNATH (International Journal of Medical Research and Review, 2023)
Acute liver failure(ALF) is defined as acute onset of hepatic dysfunction with timing of 8-28 days between onset of jaundice and hepatic encephalopathy .It is a medical emergency which needs prompt diagnosis and appropriate management with identification of the aetiological factors. I present an interesting case of acute liver failure due to cytomegalovirus(CMV) hepatitis in an immunocompetent, non addict patient without any co morbidities .The patient recovered with supportive treatment and did not require anti viral therapy as he was not immune compromised. The importance of the case lies in the fact that viral hepatitis by CMV can present in immune competent patients also and other treatable causes of acute liver failure should also be identified as several patients of ALF may need liver transplantation.